The Effects of Infection Control Teaching on the Knowledge and Performance of Hemodialysis Nurses in Tabriz - E Bagheban Karimi; S Lakdizaji; V Zamanzadeh; H Hasankhani (Iran University of Medical Sciences, 2018)
Abstract Background & Aim: Infection is the most common cause of hospitalization in hemodialysis patients and has become the second major cause of death. Lack of hygiene by staff increases the chance of infection. This study aimed to investigate the effect of infection control on the knowledge and performance of hemodialysis nurses in Tabriz. Materials & Methods: This randomized clinical trial study was conducted on 48 hemodialysis nurses in Tabriz, 2016. Nurses were randomly divided into the two groups of intervention (n = 27) and control (n = 21). Data were collected, using demographic form, a questionnaire of awareness of infection control, and checklist of performance. Training program was administered through face-to-face training and providing training package. Questionnaire and checklist were completed prior to and after the intervention in both groups. Data were analyzed using descriptive and inferential statistics with SPSS 18. Results: The two groups were not different in terms of demographic data. The average score of knowledge and performance of the two groups before and after intervention was not significantly different. Educational intervention increased knowledge (P = 0.050) and practice in hand washing (P = 0.001), disinfection of the dialysis unit (P = 0.001), use of catheter (P = 0.011), and needle insertion or removing of fistula (P= 0.001) in the intervention group. Conclusions: Infection control training can increase knowledge and performance of hemodialysis nurses. Given the importance of awareness and performance of nurses about infection control methods, training courses to enhance their knowledge and improve their performance seems essential.